The Community Structure Of Mangrove Vegetation In Rindu Laut Of Purnama Village Of Dumai City - Nico Rahmadany; Aras Mulyadi; Afrizal Tanjung (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was done in June 2014 in Rindu Laut coast of Purnama Village of Dumai City. The field sampling was using the method Line Transect Plot. The mangrove in the study area had 6 families with 10 species, i.e. Xylocarpus granatum, Rhizopora apiculata, Bruguiera gymnorrhiza, Bruguiera cylindrica, Ceriops tagal, Lumnitzera littorea, Avicennia marina, Sonneratia alba, Excoecaria agallocha and Nypa fruticans. The mangrove species that dominated in this area was Xylocarpus granatum and Rhizopora apiculata. Based on the diversity, density and water quality parameters indicated the condition of the mangrove in the study area of was at the medium stage. Parameters of the environment enough to support the growth and development of mangrove forests, it can be seen from the condition of aquatic and a substrate muddy bottoms. The calculation of the value of the dominance Index (C) ranged from 0.16 to 0.58, indicating no type of mangrove species dominating the study area.Keywords: mangrove, the structure of the community, diversity, Rindu Laut, Dumai